Effects of Different Heart Dimensions on Race Performance in Thorougbred Race Horses - Pınar, Orhan; Sancak, Aziz Arda (Acta Scientiae Veterinariae, 2018)
Background: Athletic superiority could be present in horses with a specific cardiac phenotype that differs between race types. Measurement of chamber dimensions is considered one of the most important tools for assessing heart disease severity and prognosis as well as for evaluating cardiac responses to training and detraining. The purpose of this study was to evaluate the changes of cardiac dimensions and pathological finding in intensive exercise of Thoroughbred horses on their race performance by using the 2-D Doppler and M-Mode echocardiography according to their age, body weight and sex. Materials, Methods & Results: Thoroughbred horses (40 females and 40 males) in the facilities, Ankara and Istanbul of Racetract, of Jockey Club of Turkey were included in the study. Horses were assigned as 4 study groups according to their ages and body weight separately. Group IV and I non-race horses were >7 year-old and >490 kg, >1 to ≤2 and ≤ 390 kg, Group II and III race horses were >2 to ≤3 and >390 kg to ≤ 440 kg, >3 to ≤6 year-old and >440 kg to ≤490 kg, respectively. Intensive exercise was applied to horses except group IV. The relationships between selected echocardiographic variables according to horse age, body weight and sex were analysed. Specifically left ventricle (LV) assessment by diameter in systole and diastole (LVDd and LVDs) and posterior wall thickness (LVWs and LVWd), interventricular septal thickness (IVSd and IVSs), ejection fraction (EF), fractional shortening (FS), Stroke Volume (SV), cardiac output (CO) and left ventricle mass (LVM) were determined. Descriptive statistical analyses, including mean and standard deviation were used to summarise the data. Significant differences of LVDd (P < 0.001), LVDs (P < 0.001) and SV (P < 0.001) were only determined in group I compared to group IV non-race horses. Significant differences in values of CO (P < 0.001) was determined in group III compared to group II race horses, which shows the eccentric left ventricle hypertrophy developed in Thoroughbred horses during years of racing, especially more than 4 years old of intensive exercise. Present study indicated that linear relationships between echocardiographic variables and age (P < 0.001) and body weight (P < 0.001) were found, with the linear relationships between echocardiographic variables and age being stronger than those with body weight. Discussion: Relationships between echocardiographic measurements and body weight (BW) seem to be stronger than those with age. In horses, the effects of training and growth on echocardiographic measurements have been documented, and the influence of breed has been suggested by several authors. Also, it has been demonstrated that an eccentric cardiac hypertrophy occurs in response to race training attributable to an increased diastolic stress and thus, higher heart chambers are expected in the trained Thoroughbreds and Standardbreds horses. The lack of significant differences between age groups in several LV performance indices, such as FS% and EF% might indicate that the values reported here can be extrapolated to Thorougbred horses of different ages and BW. The homogeneity of racehorse management and their closed breeding population should allow unique insights into the subtle differences in cardiac adaptations that might be associated with small differences in training horses for different race disciplines.